Transport of Particulate Matter in the Pampas/Peru District During August and September 2024 - Angeles Suazo, Julio; Angeles Vasquez, Roberto Julio (Anuário do Instituto de Geociências, 2025)
This contribution evaluates the transport of particulate matter in the district of Pampas during August and September 2024, located in the department of Huancavelica - Peru. To estimate the air quality, the Ministerio do Ambiente methodology is used for particles in fine and coarse mode. Results from August to September 2024 demonstrated the air quality was poor for fine mode particulate matter. Therefore, it is concluded that the environment for the months of August and September was harmful to people’s health, and underlines the importance of addressing air quality not only as a public health problem, but also as a critical factor in sustainable development.